Urban landscape entomology - Held, David W. (David Wayne), 1972- (Academic Press, 2019)
Urban Landscape Entomology provides readers with the background needed to adequately understand and manage many of the complexities of urban landscape pest management. For those who need training in landscape entomology, this work serves as a practical guidebook and resource. Its chapters include quality color images of pests, along with pest management tactics, such as tree injection procedures. This topical arrangement facilitates easy extraction of information relevant to a particular situation (e.g., management of borers) and uses practical terms without oversimplifying the subject matter. This work is an invaluable resource for practitioners of landscape entomology, including technicians and operations that service local landscape management needs, such as horticultural and turfgrass management. In addition, it is also a useful reference for advanced courses in landscape entomology.